Reimagining Workshops. (October 2022) - Shepley, Mardelle McCuskey; Savage, Troy; Smith, Judy
Design charettes have been a mainstay in architectural and design practice. Although they are relatively common, research studies on their effectiveness and methods are rare. Recently, an approach has been introduced in the format of Reimagining Workshops (RWs), a charette characterized by both practical and blue-sky thinking, training in empathy, and multi-stakeholder input. In spring of 2021, two RWs were held to explore ideal neonatal intensive care environments. The RWs were born out of a desire to provide a source of information for the Facility Guidelines Institute Guidelines. To date, there have been four RWs: Reimagining the ED, Reimagining Childbirth Facilities, Reimagining Critical Care, and Reimagining the NICU (virtual). This experience enables participants to operate outside of their comfort zone, an important step toward achieving innovation. They are unique in the following ways: (1) the assignments are broad, (2) participants are encouraged to think radically, (3) there are no constraints, (4) participants receive empathy training, and (5) multiple facilities and stakeholders are brought together rather than focusing on a single facility. This article describes the history of design charettes, the history of the RWs, the methodology associated with RWs, and the specific findings from the NICU and the other workshop events.